The Representation of Kidungan as an Effort to Preserve Oral Tradition in Kajoran Village: Representasi Kidungan Sebagai Upaya Menjaga Tradisi Lisan Di Desa Kajoran - Umi Umi Hanifah; Prissilia Prahesta Waningyun; Rissa Filyang (Bestari: Jurnal Pendidikan dan Kebudayaan, 2026)
This study aims to describe the role of Kidungan in efforts to preserve and transmit oral traditions across generations in Kajoran Village. The study employs a descriptive qualitative method with an ethnographic approach and a case study strategy. The research was conducted at the Kajoran Village Hall, the home of Mr. Parlan, and the home of the Village Head in Kewao Hamlet. The primary data consist of texts, audio recordings of Kidungan performances, and interviews. Data sources include community figures, customary leaders or village elders, performing artists or Kidungan singers, younger generations, village government officials or cultural practitioners, and local residents. The findings of this study indicate that Kidungan in Kajoran Village serves a variety of functions: transmitting moral values, reinforcing cultural identity, conveying oral history, fulfilling social functions within community life, providing lessons for future generations, and disseminating information about culture and history. The Kidungan tradition holds significant importance for the community, particularly as a means of affirming that Javanese culture embodies values that are adiluhung profoundly refined, noble, and dignified. More specifically, Kidungan is practiced within socio-cultural contexts at both the hamlet and village levels. At the hamlet level, it appears in activities such as tayuban, bayen, and puyen, while at the village level it is employed in rituals such as ruwat bumi, kirab, the tulak balak tradition, and the celebration of the Saka New Year. This study also finds that the continuity of the Kidungan tradition is shaped by the active involvement of community figures in Kajoran Village in transmitting it to younger generations, despite the challenges posed by modernization and social change. Accordingly, the scholarly contribution of this research lies in mapping the functions, contexts of use, and mechanisms of transmission of Kidungan as an oral tradition one that may serve as a model for cultural preservation in an era of rapid change.